PYTHON DASTURLASH TILIDA RAQAMLI TASVIRLARNI QAYTA ISHLASH KUTUBXONALARI - Medatov, A.A.; Abduvaliyev, M.M. (SCIENCE and SOCIETY, 2024)
This article shows the capabilities of OCR technologies in recognizing texts on digital images. Methods for recognizing text in an image using the Open CV, Pytesseract, EasyOCR, and Pillow libraries of the Python programming language are shown.